A sloshing induced Tsunami: 2018 Palu Bay event. (December 2021) - Han, Peida; Yu, Heng; Yu, Xiping
Abstract: A disastrous tsunami is generally known as the ocean water response to an offshore fault rupture as the consequence of a submarine earthquake. Such a physical understanding, however, cannot explain the generation of the 2018 Sulawesi earthquake induced Palu Bay tsunami. In this study, it is demonstrated that the sloshing effect dominates a tsunami event if it occurs in a semi-closed water body near the epicenter and the ground motion triggered by the earthquake is strong enough in the horizontal directions. The 2018 Palu Bay tsunami became disastrous since the sloshing effect played a significant role while landslides also contributed to the big runup at some particular locations. The present study is significant since sloshing is usually considered to play a minor role in amplifying a tsunami wave and has not been included in existing tsunami warning systems. Owing to such a limitation, the 2018 Palu Bay tsunami event was not correctly predicted at all. To prevent a future tragedy, an urgent update of the worldwide tsunami warning system in service may have to be performed to include an option for possible consideration of the sloshing effect.